2008
DOI: 10.1007/s00428-008-0697-3
|View full text |Cite
|
Sign up to set email alerts
|

Renal angiomyoadenomatous tumor: morphologic, immunohistochemical, and molecular genetic study of a distinct entity

Abstract: We present a series of a distinct tumorous entity named renal angiomyoadenomatous tumor (RAT). Five cases were retrieved from the consultation files of the authors. Histologic and immunohistochemical features were evaluated. Sequencing analysis of coding region of the VHL gene was carried out in all cases. The tumors were composed of admixture of an epithelial clear cell component and prominent leiomyomatous stroma. Epithelial cells formed adenomatous tubular formations endowed with blister-like apical snouts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 22 publications
3
72
3
4
Order By: Relevance
“…Often the epithelium demonstrated a tufted growth into the lumen of the glands with an ill-defined apical cytoplasmic border, similar to the 'blister-like' appearance described by Michal et al 3 Surrounding the epithelial elements, a layer of capillaries was often prominent, imparting a dualcell layer pattern resembling a basal cell or myoepithelial cell layer. The endothelial nature of these cells was supported by immunohistochemistry for CD34, with some areas showing an interrupted or discontinuous capillary network surrounding the glands.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Often the epithelium demonstrated a tufted growth into the lumen of the glands with an ill-defined apical cytoplasmic border, similar to the 'blister-like' appearance described by Michal et al 3 Surrounding the epithelial elements, a layer of capillaries was often prominent, imparting a dualcell layer pattern resembling a basal cell or myoepithelial cell layer. The endothelial nature of these cells was supported by immunohistochemistry for CD34, with some areas showing an interrupted or discontinuous capillary network surrounding the glands.…”
Section: Discussionsupporting
confidence: 59%
“…[1][2][3][4] However, the relationship of these tumors to other renal epithelial neoplasms, particularly clear cell renal cell carcinoma 4 and clear cell papillary renal cell carcinoma, 5-11 is incompletely understood. 13 To shed light on these relationships, in this study we assessed clinicopathological, immunohistochemical, and molecular features of renal epithelial neoplasms with a prominent stromal smooth muscle component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Michal et al 23 similarly reported the 'renal angiomyoadenomatous tumor,' which has subsequently been studied by other authors. [24][25][26][27][28][29] Although a link to clear cell papillary renal cell carcinoma has been proposed, 29 the relationship of these entities remains uncertain. 4,24 At least some of these lesions have demonstrated abnormalities of chromosomes 3 and the VHL gene, in addition to chromosomes 1, 11, and 16.…”
Section: Discussionmentioning
confidence: 99%
“…One such subtype is clear-cell papillary renal cell carcinoma, a typically low-grade renal epithelial neoplasm with morpho-logical features mimicking both clear-cell renal cell carcinoma and papillary renal cell carcinoma that also occasionally exhibits prominent smooth muscle metaplasia within the intratumoral stroma. We, and others, believe that a variety of other recently described entities, including renal angiomyoadenomatous tumor, 2 clear-cell tubulopapillary renal cell carcinoma, 3 renal cell carcinoma with prominent leiomyomatous proliferation 4 and clearcell renal cell carcinoma with diffuse cytokeratin 7 immunoreactivity 5 are either closely related, if not the same, tumors as clear-cell papillary renal cell carcinoma described in the literature with alternative nomenclature. 3,[5][6][7][8] Our contention is further supported by presentations at the most recent annual meeting of United States and Canadian Association of Pathologists (USCAP, 2011) regarding clear-cell papillary renal cell carcinoma and renal angiomyoadenomatous tumor.…”
mentioning
confidence: 86%